2013
DOI: 10.1118/1.4774053
|View full text |Cite
|
Sign up to set email alerts
|

Position sensitive measurement of lithium traces in brain tissue with neutrons

Abstract: The combination of a very high lithium sensitivity with position resolving measurement makes this method well suited for postmortem studies of the microscopic lithium distribution in the human brain and thus to form a microscopic picture of the impact of lithium in different areas of the human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…For quantitative analysis, the spectra of a Li reference sample coated by vapor deposition with a well‐defined amount of Li ( λ ref =50 μg LiF nat cm −2 ) was used. The basic concept of the detection method and its specific application for Li‐ion battery electrodes was described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…For quantitative analysis, the spectra of a Li reference sample coated by vapor deposition with a well‐defined amount of Li ( λ ref =50 μg LiF nat cm −2 ) was used. The basic concept of the detection method and its specific application for Li‐ion battery electrodes was described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The detector as well as the target are tilted by y = 251 with respect to the axis of the neutron beam. 60 For quantitative analysis, the spectrum of a Li reference sample coated by vapor deposition with a well-defined amount of Li (l ref = 50 mg LiF nat cm À2 ) has been used. Fig.…”
Section: Triton Analysismentioning
confidence: 99%
“…Lithium medication is also associated with thyroid [ 28 ] and kidney dysfunction [ 29 ]. In spite of these previous findings, no study has reported lithium distribution in the body, except in the brain and in serum, with capillary ion analysis [ 30 ] and neutron capture reaction [ 31 ], respectively.…”
Section: Introductionmentioning
confidence: 99%